Student Hostel Accomodation Challenge in Benue State University, Makurdi and The Public-Private Partnership Option - Utile, Timothy (Brawijaya Journal of Social Science, 2024)
One of the most cherished educational assets for students in tertiary institutions in Nigeria and the world is hostel accommodation. This asset provides students with an environment for intellectual development and easy interaction with fellow peers and fosters teamwork and communal spirit among students. Hostel accommodation in most Nigerian tertiary institutions is problematic and scarce too; as such, many students tend to be affected academically and psychologically; this study investigated the challenges of hostel accommodation in Benue State University, Makurdi and suggested the Public Private Partnership (PPP) option. The objectives of the study are to ascertain the causes of hostel accommodation challenges in Nigerian tertiary institutions with Benue State University, Makurdi, in sight, to ascertain the impact of hostel accommodation problems on students' academic performance and welfare and to suggest options best for hostel accommodation challenge in Nigeria tertiary institution. Three research questions guided the study. The study is anchored on the stakeholders' theory by Edward Freeman (1983). A mixed-method research design was adopted for this study. Simple random sampling was used, and questionnaire administration and Oral interviews were conducted to obtain information from 45 respondents. The study found out, among other things, that the over-enrollment of students causes a shortage in student hostel accommodation, inadequate hostel facilities, and a lack of maintenance culture by management/government, which are identifiable sources of accommodation challenges. The study recommends the PPP option and privatization of hostel facilities as the way forward for the best quality and quantity of accommodation in tertiary institutions in Nigeria.